Advancing Global Health - The Need for (Better) Social Science; Comment on "Navigating Between Stealth Advocacy and Unconscious Dogmatism: The Challenge of Researching the Norms, Politics and Power of Global Health" - Johanna Hanefeld (Kerman University of Medical Sciences, 2016)
In his perspective "Navigating between stealth advocacy and unconscious dogmatism: the challenge of researching the norms, politics and power of global health," Ooms argues that actions taken in the field of global health are dependent not only on available resources, but on the normative premise that guides how these resources are spent. This comment sets out how the application of a predominately biomedical positivist research tradition in global health, has potentially limited understanding of the value judgements underlying decisions in the field. To redress this critical social science, including health policy analysis has much to offer, to the field of global health including on questions of governance.